Frequency of HEV contamination in sewerage waters in Pakistan - Ahmad, Tahir; Waheed, Yasir; Tahir, Sadia; Safi, Sher Zaman; Fatima, Kaneez; Afzal, Muhammad Sohail; Farooqi, Zia-ur-Rehman; Qadri, Ishtiaq (The Journal of Infection in Developing Countries, 2010)
Introduction: Enteric viruses, including Hepatitis E virus (HEV), are able to persist under environmental conditions and may cause public health problems by contaminating natural and drinking water resources. Routine procedures for monitoring viruses in water samples have not been established for the water microbiology screening panel. Methodology: Eighty-six raw sewerage samples were collected from the different regions of Islamabad and Rawalpindi, the twin cities of Pakistan. Samples were concentrated for HEV, using a polyethylene glycol-based method followed by viral RNA extraction using a commercial kit-based method. Reverse transcription polymerase chain reaction (RT-PCR) with HEV specific primers was used for the detection of HEV. Results: The present investigation focused on 86 raw sewerage water samples taken from different locations of drainage outlets of Islamabad and Rawalpindi. After careful experimentation, 35 samples were found to be RT-PCR positive. Nineteen (44.7%) out of 47 samples from Rawalpindi city were HEV positive while 16 (41.02%) out of 39 samples from Islamabad were HEV positive. All positive samples were found in the highly congested areas. Conclusions: The high detection rate of HEV in this study shows that HEV circulates at a relatively high frequency in the sewerage waters in Pakistan. This study is the first report on detection of HEV from sewerage waste water from Pakistan and suggests that HEV might be a potent indicator of viral pollution in environmental specimens.